Social Inequalities and the Reform of Romanian Public Pension System by Law no. 127/2019 - Nicolae Balteș; Ștefania Amalia Jimon (Ovidius University Annals: Economic Sciences Series, 2019)
Social protection system had developed in order to ensure the protection of the citizens, but also to maintain the economic growth of the country. The importance of the pension system is given by its social purpose, which is poverty alleviation, adequacy of income and consumption smoothing at retirement. In countries of Central and Eastern Europe, the income inequalities – main cause of poverty, had increased with the economic development. The aim of this paper is to show the changes brought to Romanian public pension system by the Law no. 127/2019 regarding the provided benefits vis-à-vis of social inequalities existing among elderly people.